Evaluating the impact of translational research enrollment on the patient care experience of Veterans with prostate cancer who receive care through the Veterans Affairs (VA) healthcare system - Hamilton, Ian; Pollen, Joel; Lesnik, Dyan M.; Kosoff, David (Journal of clinical oncology, 2024)
e23210Background: Veterans with cancer represent a unique subset of patients with distinct exposure histories and cancer epidemiology. Translational research studies that incorporate Veteran-derived biospecimens are therefore critical to advance our understanding of Veteran cancer biology and improve treatment options for Veterans with cancer. Biospecimen-based translational studies also offer an opportunity to enhance the Veteran care experience by enabling Veterans to directly contribute to cancer research efforts. While the biologic benefits of biospecimen research have been well established, the benefit of translational research on the Veteran care experience has yet to be defined. In this study, we evaluated: 1. Whether Veteran enrollment in a biospecimen-based prostate cancer research study improved their VA patient care experience and satisfaction and 2. Whether a VA-based data analyst tool could be used to optimize patient enrollment in translational research studies. Methods: Beginning in January, 2022, Veterans with a diagnosis of prostate cancer receiving care at the William S. Middleton VA were enrolled in a translational research study that collected blood and tissue biospecimens for subsequent investigation and analysis. After at least 30 days of enrollment, subjects were sent an anonymous survey inquiring about how participation in the translational research study impacted their VA care experience and healthcare satisfaction. To optimize enrollment in the study, an ICD-9 code search function was employed within the medical record database to readily identify eligible VA clinic patients based on an active prostate cancer diagnosis. Descriptive analyses were performed using Prism statistical software. Results: Nearly all Veterans who responded to the questionnaire agreed that participation in translational research was a meaningful experience that increased their satisfaction with their VA medical care. In addition, a vast majority of Veterans surveyed felt that their research participation could help improve care for other Veterans, and most expressed willingness to participate in future VA research opportunities. In a secondary analysis, our ICD-9 search function accurately identified eligible VA clinic patients with a prostate cancer diagnosis, and implementation of this tool has saved approximately 30 minutes of weekly physician and research coordinator work compared to manual chart review. Conclusions: Veteran enrollment in translational research studies provides a meaningful experience for Veterans that can lead to increased satisfaction with the VA healthcare system. Future VA initiatives to improve the Veteran care experience should focus on expanding translational research opportunities for Veterans as well as addressing potential barriers to enrollment.